KEANEKARAGAMAN DAN AKTIVITAS KUMBANG KURA-KURA (TORTOISE) PADA TANAMAN KANGKUNG PAGAR (IPOMEA CARNEA) DI MADIUN - Ganjari, Leo Eladisa (Widya Warta, 2016)
This study aimed (1) to determine the diversities and activities of tortoise beetles on fence kale plants (Ipomea carnea) in Madiun and (2) to analyze their ecological effects on the environment. This research was conducted from January up to September 2014 in the Madiun town. The method used was the location tracer of fence kale plants and identification as well as observation on the activities of tortoise beetles. The data were analyzed descriptively. The results revealed that (1) there were two kinds of tortoise beetles on the fence kale plants - Aspidomorpha sanctaecrucis Fabricius and Aspidomorpha miliaris Fabricius, whose activities became pests on the fence kale plants. The activities of Aspidomorpha sanctaecrucis Fabricius were more dominant; and ecologically the tortoise beetles as pests of leaves inhibited the growth and development of the fence kale plants only, but not the other plants around them. And, parasitic symbiosis occurred between the tortoise beetles and the fence kale plants